(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
This research evaluates the relationship between transparency and social participation, highlighting the importance of ICTs to promote transparency in public management. The study analyze the open data portals of five Brazilian states, randomly selected from different regions of the country. Open data policies were evaluated in terms of arrangement between government bodies, adoption of standardized technology, existence of official repositories, institutionalization of data openness and promotion of data use. The methodology involved bibliographic and documentary research on government portals to identify publication standards, availability and compliance with open data principles.